Assessing the Longer‐Term Effects of Mild Traumatic Brain Injury on Self‐Reported Driving Ability. Issue 11 (17th May 2018) - Bernstein, John P.K.; Calamia, Matthew
Abstract: Background: Mild traumatic brain injury (mTBI) can have long‐term cognitive and functional consequences, and recent mTBI has been associated with impaired performance on measures related to driving ability. However, it remains unclear whether mTBI history is associated with poorer driving performance. Objective: To examine the longer‐term effects of mTBI on self‐reported driving ability. Design: Retrospective cross‐sectional study. Setting: Online. Participants: Three hundred eighty‐nine participants (169 who reported an mTBI history and 220 without an mTBI history). Intervention: Comparing participants who report a history of mTBI with those who do not report a history of mTBI. Outcomes: Self‐report measures of mTBI history, frequency of aberrant driving behaviors, recent history of car accidents and citations, and previous psychological diagnoses and current symptoms. Results: Participants with a history of mTBI reported an overall higher frequency of aberrant driving behaviors and committing more driving violations that risked the safety of others than comparison participants. Participants with mTBI also were more likely to have been involved in a car accident within the past 6 months and the past 3 years. Of participants with mTBI, reports of driving violations decreased with longer time since the most recent injury. Driving violations and crash risk also decreased with increased age and years of driving experience. Conclusions: Individuals with a history of mTBI are more likely to deliberately drive in a manner that risks the safety of others and are at a heightened risk of being involved in a recent car crash. Future work should examine predictor variables in greater depth and incorporate performance‐based measures of driving ability to further explore these topics. Level of Evidence: III